An Experimental Investigation On Pull Through Failure Of Roof Cladding To Purlin Connection Considering Overhang Roof - Ahmad, Nik Aisyah Sofea Nik (Universiti Sains Malaysia, 2019)
The study of effects on wind loading to the roof cladding and purlin connection become the focus of the present study. It is found that the failure of roof cladding initiated at the overhang roof due to turbulence created form the strong wind. However, the previous studies are limited to the non-engineered building without overhang roof mainly the rural house in northern region of Peninsular Malaysia. In this study, the typical overhang roof length was obtained through rural house survey. The experimental study using simple pull through test was performed to simulate the wind loading effect on rural house features especially at overhang roof. Therefore, the study is conducted to investigate the pull through capacity on cladding to purlin connection of rural house. The tests were conducted on two types of claddings namely, corrugated and trapezoidal roof cladding. The purlin used timber type Dark Red Meranti which classified under strength group 5 and the wind loading was applied via hydraulic jack machine. In the case of corrugated roof cladding, the highest pull through capacity exhibited by 0.28 mm thickness with 200 overhang length (1.534 kN) followed by 0.28 mm thickness with 300 mm overhang length (1.083 kN). Meanwhile, the maximum applied load exhibited by 0.28 mm thickness with 200 mm overhang length (3.391 kN) followed by 0.28 mm thickness with 300 mm overhang length (2.830 kN). In the case of trapezoidal roof cladding, 0.35 mm thickness of 300 mm overhang exhibited the highest pull through capacity (1.153 kN) followed by 0.35 mm thickness of 200 mm overhang length (kN). However, the maximum applied load exhibited by 0.35 mm thickness with 200 mm overhang length (3.738 kN) followed by 0.35 mm thickness of 300 mm length of overhang (3.589 kN). It was noted that shorter length of overhang developed stronger roof cladding to purlin connection. The most efficient connection for roof cladding to purlin connection was found to be 0.23 mm thickness of corrugated roof cladding with 200 mm overhang length.